Immune response to hepatitis B surface antigen. - Ibrahim, A B (1975)
A total of 69 persons were investigated for assessment of cell-mediated and humoral immunity to hepatitis B surface antigen (HBsAg). Three groups, each consisting of 20 normal persons, 20HBsAg carriers, and 20 convalescent hepatitis B patients, were studied for HBsAg, anti-HBs, and leukocyte migration inhibition with purified HBsAg. Sequential sampling if an additional group of nine acute hepatitis B patients defined the cellular and humoral immune response to HBsAg. The antigen was eliminated rapidly by mounting of cell-mediated immune response detectable for a limited period, followed by antibody response in relatively few patients moore than 3 months after clearance of circulating HBsAg.